Human tubal secretion can modify the affinity of human spermatozoa for the zona pellucida - Munuce, María José (2009)
Objective: To study the effect of the human tubal tissue conditioned medium (CM) on sperm parameters related to sperm-zona pellucida interaction. Design: Controlled experimental laboratory study. Setting: Research laboratory. Subject(s): Semen samples from donors with normozoospermia. Human tubal tissue obtained from women undergoing hysterectomies. Human follicular fluids (hFF) and oocytes collected from patients undergoing IVF-ET. Intervention(s): Incubation of spermatozoa with CM proteins obtained from human tubal tissue culture; sperm binding to the zona pellucida assessment. Main Outcome Measure(s): Explants' viability was assessed by tissue DNA analysis. Sperm ability to interact with zona was tested with use of the whole oocyte test. Expression of d-mannose binding sites was assessed with use of a fluorescent probe on mannose coupled to bovine serum albumin. Human FF-induced acrosome reaction was assessed by the Pisum sativum technique. Result(s): Although treatment with 0.8 μg/μL of CM allowed sperm binding to the zona and the expression of d-mannose binding sites comparable with sperm in control medium, with 3.2 μg/mL of CM resulted in a significant decrease of both parameters. No effect of CM on spontaneous or hFF-induced acrosome reaction or in sperm viability was observed. Conclusion(s): The results indicate that the incubation of spermatozoa in the presence of CM reduces sperm affinity for the zona pellucida. This effect can be partly explained by the decreased expression of d-mannose binding sites on the sperm surface.